Implementasi Proses Rekrutmen Pada PT. BFI Finance Tbk Area Sumbagut Cabang Padang Sidimpuan - Rachmawati, Yeni; Mudrikah, Silvi (Cattleya Darmaya Fortuna, 2024)
Human Resources (HR) is the main factor in a company. It helps the company to optimally realize its expected goals. Obtaining good qualifications is the goal achieved in the Implementation of the Recruitment Process of PT BFI Finance Indonesia Tbk Area Sumbagut Padangsidimpuan Branch. Researchers collected data from interviews, observations and data based on research, using indicators of the recruitment process variable, namely Identifying vacant positions, searching for position information through position analysis, determining the right source of candidates, choosing the most appropriate recruitment method, calling candidates who meet the qualifications or requirements, making job offers and starting work. This type of research is descriptive with a qualitative approach. . The recruitment is carried out according to the needs of the company or when the company needs employees, through internal and external sources the company also cooperates with parties looking for workers and also determines the qualifications that are in accordance with the criteria needed by the company. the recruitment of employees is carried out to obtain human resources or prospective employees who are qualified, competent and in accordance with the required qualifications, although in the recruitment process there are obstacles that are not in accordance with the wishes of the company. the company still tries to recruit more precisely on target.